Attention Deficit Hyperactivity Disorder and oxidative stress: A short term follow up study. Issue 1 (30th September 2015) - Guney, Esra; Cetin, Fatih Hilmi; Alisik, Murat; Tunca, Huseyin; Tas Torun, Yasemin; Iseri, Elvan; Isik Taner, Yasemen; Cayci, Banu; Erel, Ozcan
Abstract: In this study, we aimed to investigate total antioxidative status (TAS) and total oxidative status (TOS) of plasma and antioxidant enzymes such as paraoxonase (PON), stimulated paraoxonase (SPON), arylesterase (ARES) and thiols in plasma of children and adolescents with Attention Deficit Hyperactivity Disorder (ADHD). In the second step. this study aimed to reveal the possible effects of ADHD treatment on these parameters. Fifty-six patients with ADHD and 52 healthy controls were involved in this study. Venous blood samples were collected and oxidative and antioxidative parameter's were studied. In the second phase of the study, blood samples were taken from patients using medication. Pre-treatment oxidative stress index (OSI) values and the plasma TOS levels of the patients with ADHD were statistically higher than those of the control group. The plasma thiol levels of the patients with ADHD were significantly lower than the control group. The post-treatment plasma antioxidative parameter's levels were significantly higher than the pre-treatment levels. The post-treatment oxidative stress index value was significantly lower than the pre-treatment value. Therefore, oxidative metabolism was found to be impaired in children and adolescents with ADHD. It was also determined that methylphenidate repairs the oxidative balance by increasing antioxidant defence mechanisms. Highlights: Oxidative metabolism was found to be impaired in children and adolescents with ADHD. Methylphenidate repaired the oxidative balance by increasing antioxidant defense mechanisms. Post-treatment plasma oxidative stress index were similar to the control group. This is the first study investigating the effects of methylphenidate on oxidative metabolism in humans.